Analysis of The Influence of Influencer Marketing, Brand Image, Customer Review, and Price Discount on E-Commerce Shopee Purchase Decision - Devna Ramadhani; Mirwan Surya Perdhana (Diponegoro Journal of Management, 2025)
This study examines the impact of influencer marketing, brand image, customer reviews, and price discounts on skincare purchasing decisions on Shopee Indonesia. It uses a case study approach, focusing on Skintific (an international brand) and Wardah (a local brand), to analyse consumer purchase intentions and the influence of independent variables on the dependent variable. A mixed-method explanatory sequential design was used, combining quantitative data from 220 Shopee users and qualitative data from in-depth interviews with selected consumers of both brands. Data analysis was conducted in SPSS, using validity and reliability tests, multiple regression, t-tests, and F-tests. Results indicate that Indonesian consumers generally prefer international skincare brands. Qualitative data gathered from four informants through online interviews were analysed using comparative methods and triangulation to support the quantitative findings. The study confirms that all four factors significantly influence purchasing decisions, with customer reviews being the most impactful. These findings provide valuable guidance for skincare brands in shaping effective digital marketing strategies on e-commerce platforms and contribute to research on online consumer behaviour in the beauty industry.